Irregularity index for quick identification of worst column removal scenarios of RC frame structures - He, Xiao-Huang-Can; Yuan, Xian-Xun; Yi, Wei-Jian (Engineering structures, 2019)
•An index was proposed to measure geometrical irregularity of RC frame structures.•The index, Π was derived by yield line mechanism and tensile membrane action.•Very high correlation exists between Π and collapse resistance of frame structures.•The index can be used to identify the worst column removal scenarios of RC frames. Irregular structures are known to be more prone to disproportionate collapse (DC) than structures with regular horizontal and vertical layouts. Despite this, many public, commercial and institutional buildings have to be designed with various irregularities in structural layout due to architectural and aesthetic considerations. While extensive experimental and numerical studies have been carried out to advance the basic understanding of DC behaviors of regular structures, limited research has been carried out on irregular structures. On the other hand, alternate load path method has been recommended by several design codes and standards for DC design, but the large number of potential column removal scenarios involved poses a real challenge for the wide use of the method. This paper presents a quantitative measure referred to as irregularity index, or Π, that can be used to quickly identify the worst column removal scenarios for design check of DC resistance of reinforced concrete (RC) frame structures. Based upon a solid understanding of various competing failure mechanisms and DC resistance of RC frame structures, the irregularity index was derived from the maximum load factors between the yielding load and the limit load at the end of tensile membrane action stage. For verification and validation of the proposed Π, a 3D nonlinear finite element model was developed in OpenSees and calibrated by beam-slab sub-assemblage experiments. Various numerical experiments were carried out to verify the effectiveness of the Π. The very high correlation coefficient between the calculated irregularity indices and DC resistance obtained from finite element analyses showed that the proposed irregularity index can quickly identify the worst column removal scenarios in various irregular structures including setback buildings and large-bottom-space structures. Sensitivity analysis further verified the reliability of the proposed irregularity index.